Molybdenum accumulation in sediments a quantitative indicator of hypoxic water conditions in Narragansett Bay, RI - Boothman, Warren S (Estuarine, coastal and shelf science, 2022)
Authigenic molybdenum (Mo) accumulation in marine sediments has often been used as a qualitative indicator of hypoxic bottom water. To investigate its use as a quantitative indicator of hypoxic exposure, sediment cores were collected from water quality monitoring sites in Narragansett Bay (RI, USA) that experience varying periods of hypoxia. Total Mo concentrations in surficial (0-1 cm) sediments were determined by total digestion and ICP-MS analysis. Lithogenic contributions to total Mo concentrations were estimated by multiplying measured concentrations of aluminum (Al) by the mean crustal Mo:Al ratio and subtracting them from the total concentrations to yield the authigenic fraction. 210Pb dating was used to determine sediment accumulation rates at each site. Mean annual periods of hypoxia in bottom waters were determined from continuous monitoring data for the years coinciding with the top 1 cm of sediment. Results indicated a linear relationship between authigenic Mo concentrations and frequency of hypoxia, although the relationships differed between different sampling periods. These results demonstrate the potential of sedimentary Mo as a tool for assessing the spatial and temporal extent of hypoxia in coastal waters